Alienation and authoritarian appropriation - the spatiotemporality of political subjectivation under East German urban neoliberalism = Entfremdung und autoritäre Aneignung - die Raum-Zeitlichkeit politischer Subjektivierung im ostdeutschen urbanen Neoliberalismus - Reichle, Leon Rosa (ZRex, 2024)
This paper contributes to a growing field of spatial analyses of authoritarianism by asking how urban neoliberalization impacts authoritarian subjectivation. It analyses why working class long-term tenants in a gentrifying working class district of the East German city of Leipzig are susceptible to authoritarianism. It traces how their political subjectivation operates through space and time. The theoretical contribution is a spatio-temporally sensitive theorization of subjectivation between alienation and appropriation. Tenants’ experiences of alienation and their attempts of appropriation depend on processes of political economic restructuring in a row of scales from their flat to the reunited nation, and their classed position within these. The tenants in focus develop a nostalgic temporality of belonging, reminiscent of a lost past and devoid of present engagement or an imaginable future. This fosters ideological, authoritarian forms of appropriation, reproducing social hierarchies and scapegoating instead of encouraging practical engagement with present conditions.